Biochar for crop production: potential benefits and risks - Hussain, Mubshar; Farooq, Muhammad; Nawaz, Ahmad; Al-Sadi, Abdullah M.; Solaiman, Zakaria M.; Alghamdi, Salem S.; Ammara, Ume; Ok, Yong Sik; Siddique, Kadambot H. M. (Journal of soils and sediments, 2017)
Purpose Biochar, the by-product of thermal decomposition of organic materials in an oxygen-limited environment, is increasingly being investigated due to its potential benefits for soil health, crop yield, carbon (C) sequestration, and greenhouse gas (GHG) mitigation. Materials and methods In this review, we discuss the potential role of biochar for improving crop yields and decreasing the emission of greenhouse gases, along with the potential risks involved with biochar application and strategies to avoid these risks. Results and discussion Biochar soil amendment improves crop productivity mainly by increasing nutrient use efficiency and water holding capacity. However, improvements to crop production are often recorded in highly degraded and nutrient-poor soils, while its application to fertile and healthy soils does not always increase crop yield. Since biochars are produced from a variety of feedstocks, certain contaminants can be present. Heavy metals in biochar may affect plant growth as well as rhizosphere microbial and faunal communities and functions. Biochar manufacturers should get certification that their products meet International Biochar Initiative (IBI) quality standards (basic utility properties, toxicant assessment, advanced analysis, and soil enhancement properties). Conclusions The long-term effects of biochar on soil functions and its fate in different soil types require immediate attention. Biochar may change the soil biological community composition and abundance and retain the pesticides applied. As a consequence, weed control in biochar-amended soils may be difficult as preemergence herbicides may become less effective.